Challenges and opportunities in molecular-level indoor surface chemistry and physics (2020)
The high surface-to-volume ratio that is typical indoors makes surface chemistry and physics particularly important to the study of air quality in these environments. However, surface-mediated transformations in indoor environments are not adequately understood, largely because the surfaces involved are notoriously complex. Moreover, it is challenging to capture dynamic changes in real time and under ambient conditions. This Perspective presents a path to bridge this capability gap by reviewing recent developments in advanced instrumentation and collaborative work and discussing research opportunities that have the potential to contribute new chemical and physical insights into indoor surface processes. Mechanistic studies of idealized model surfaces and on surfaces of real-world indoor samples will help us better quantify sources and sinks of indoor air pollutants, improve the prediction of dynamic changes in indoor air quality, and open the door for the design of smart coatings or paints for controlling, mitigating, or preventing the potential negative outcomes of indoor air chemistry.